Societal Development through Eco-Pesantren Programs: Actualizing the Functions of Pesantren in Empowering Society - Khoirurrijal, M Faishal; Mahfudloh, Ririn Inayatul; Rusydiyah, Evi Fatimatur (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This research analyzes social empowerment through the Eco-Pesantren program at PPTQ Al-Munawwaroh. A descriptive-exploratory approach was employed, with data obtained through interviews, questionnaires, observations, and documentation. The researchers analyzed the data using the Miles and Huberman model, comprising data reduction, presentation, and conclusion/verification. The results show that social empowerment through the program is achieved over several stages: (1) awareness through the socialization of the importance of maintaining environmental sustainability; (2) capacity development through training in managing the environment and waste; and (3) society empowerment through various programs oriented towards environmental sustainability. These programs included information on (1) the fruit and vegetable village; (2) waste bank; (3) organic waste terminal and biopore composter; (4) one student one eco brick; and (5) the movement to switch off TVs and electrical equipment from Maghrib to Isyak. The program is essential in bridging ecological activities at the grassroots level between the pesantren and surrounding communities.